Ftalimidas como anólitos em batérias de fluxo redox totalmente orgânicas - Silva, Rafaela Binda da (Universidade Federal de São Carlos, 2026)
In the context of developing sustainable materials for energy storage, phthalimides have emerged as promising candidates for application as anolytes in redox flow batteries. In this work, a large-scale computational screening of 5,705 phthalimide derivatives was performed, including a strategically designed subset of bio-based molecules derived from biomass. Structure–property analyses, grounded in principles of physical organic chemistry, were employed to elucidate trends related to redox potential and radical stability, properties that are fundamental to the performance of redox flow batteries. Statistical modeling and clustering analyses were used to refine the selection of the most promising candidates. Based on these results, four compounds with distinct properties were synthesized. Among them, the bio-based compound 8’ stood out, presenting favorable properties and being synthesized through a sustainable route involving a Diels–Alder reaction followed by aromatization. Electrochemical characterization of phthalimide 8’ revealed quasi-reversible redox behavior, high solubility in acetonitrile, and excellent stability over more than 2,000 redox cycles, with no evidence of chemical decomposition. These results highlight the potential of computational approaches to accelerate the discovery of robust, renewable, and high-performance organic materials for next-generation energy storage systems.
Phthalimides as anolytes in fully organic redox flow batteries
Keywords: Batérias de fluxo redox; Ftalimidas; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FISICO-QUIMICA ORGANICA; 7. Energia limpa e acessível